Protection motivation theory screening tool for predicting chronic low back pain rehabilitation adherence: analysis of a randomised controlled trial. Issue 2 (3rd February 2022) - Owen, Patrick J; Main, Luana C; Miller, Clint T; Ford, Jon J; Hahne, Andrew J; Belavy, Daniel L
Abstract : Objective: To explore a protection motivation theory screening tool for predicting rehabilitation adherence. Design: Analysis of a randomised controlled trial. Setting: An exercise physiology and physiotherapist clinic. Participants: Patients with chronic low back pain (n=40). Interventions: General strength and conditioning (GSC) compared with motor control and manual therapy. Primary and secondary outcome measures: predicting patient adherence to supervised sessions and dropout using the Sports Injury Rehabilitation Beliefs Scale, seven-item barriers checklist and Positive and Negative Affect Schedule and Sports Injury Rehabilitation Adherence Scale. Results: Average attendance was 77% (motor control and manual therapy) and 60% (GSC) with eight dropouts. No Sports Injury Rehabilitation Adherence Scale values other than 5 across all three components were recorded. Treatment efficacy (p=0.019), self-efficacy (p=0.001), rehabilitation value (p=0.028) and injury severity (p=0.002) positively correlated with susceptibility (the extent of vulnerability to having health problems from not taking action). Rehabilitation value positively correlated with self-efficacy (p=0.005). Injury severity positively correlated with rehabilitation value (p=0.011). The final model for number of cancellations included rehabilitation value only and accounted for approximately 12% of variance (p=0.033). Conclusions: Perceived value of rehabilitation should be considered by clinicians in the rehabilitation setting to improve treatment adherence in patients with chronic low back pain. Trial registration number: ACTRN12615001270505.